Using Finger Puppets in the Primary Care Setting to Support Caregivers Talking With Their Infants: A Feasibility Pilot Study. (May 2020) - Domek, Gretchen J.; Szafran, Lauren Heller; Bonnell, Levi N.; Berman, Stephen; Camp, Bonnie W.
Disadvantaged children often show disparities in early language development. We tested the feasibility, acceptability, and preliminary efficacy of introducing finger puppets in the primary care setting at the 2-month well visit to support caregivers talking with their infants. Caregivers completed a sociodemographic survey and were contacted by phone 2 weeks later to assess initial usage and satisfaction. Ages & Stages Questionnaires (ASQ-3) were independently recorded at well visits. A family cumulative risk score was calculated from the sociodemographic survey. Thirty-four caregiver-child pairs were enrolled. Caregivers reported high satisfaction with the intervention. ASQ-3 Communication and Total scores at 6, 12, and 18 months were significantly higher for high puppet users across all age levels with no significant interactions with age or cumulative risk. Finger puppets provide a low-cost way to promote language-rich interactions. Preliminary evidence suggests that high puppet usage may have long-lasting effects on child development and should be further evaluated.